Psychometric Evaluation of the BFI-10 and the NEO-FFI-3 in Indian Adolescents - Kunnel John, Roshin; Xavier, Boby; Waldmeier, Anja; Meyer, Andrea; Gaab, Jens (Frontiers in Psychology, 2019)
The Five-Factor Model (FFM) is one of the most commonly examined constructs of personality across cultures in recent times. However, there is a lacuna of evidence for the suitability of FFM measures for Indian adolescent school students below the age of 17 years. We carried out two independent studies for the psychometric evaluation of the measures BFI-10 and NEO-FFI-3 on Indian adolescent school students. Both studies examined two socio-culturally distinct linguistic groups of secondary and senior secondary school students with a total sample of N=1117 students. Neither of the measures had adequate internal consistency, nor consistent model fit with normative data. However, acceptable Cronbach’s alpha reliability scores were found on some personality domains, i.e., Openness and Agreeableness in BFI-10 and Conscientiousness in NEO-FFI-3 and these domains were identifiable on principal components analysis. A separate analysis of older students’ subgroup of 17-18 years yielded a better model fit for both measures and improved alpha reliability values for NEO-FFI-3. The results provide strong evidence against using adult personality measures with adolescents without separate psychometric validation​ and applying the Western age norms to Indian students without considering that the process of personality consolidation during adolescence may not be identical across cultures.